PaO2/FIO2 ratio: the mismeasure of oxygenation in COVID-19. Issue 3 (25th March 2021) - Tobin, Martin J.; Jubran, Amal; Laghi, Franco
We read with interest A. Tulaimat's letter concerning our recent editorial in the European Respiratory Journal [1]. A. Tulaimat makes several insightful comments on problems with criteria used for entering patients into randomised controlled trials of noninvasive ventilation. Among these, he notes that arterial-to-inspired oxygen ( P aO2 / F IO2 ) ratio varied between 170 and 400 among enrollees [2]. P aO2 is the most precise measurement of patient oxygenation in COVID-19, but its accuracy is corrupted when communicated as P aO2 / F IO2 ratio https://bit.ly/3tNipTJ